Constitutional Recognition of Living Law in Criminal Law: A Comparative Study of Indonesia and Southeast Asia - Ganjar Patria Lugina; Abdullah, Rahmat; Pujiyono; Sukirno; Ota Musashi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Criminal-law systems grounded in the principle of nullum crimen sine lege face a doctrinal challenge in accommodating unwritten societal norms as a source of criminal liability. Post-colonial states in Southeast Asia with pluralistic populations have developed divergent constitutional architectures for recognising living law within their criminal justice systems. Systematic comparative scholarship on the constitutional models through which Southeast Asian jurisdictions recognise living law remains limited. This article compares the constitutional construction of living law recognition in the criminal law of Indonesia, Malaysia, Brunei Darussalam, and the Philippines, identifying the constitutional bases, normative mechanisms, and implications of each model for the principle of legality, human-rights protection, and state legal sovereignty. The study employs normative legal research with the functional method of comparative law as articulated by Zweigert and Kötz. The analysis yields a typology of four constitutional limitation models: substantive limitation (Indonesia), jurisdictional limitation (Malaysia), authoritative limitation (Brunei Darussalam), and communitarian limitation (Philippines). Indonesia's dual-legality model under Article 2 of Law No. 1 of 2023 occupies the most complex position relative to the formal legality principle, while incorporating substantive human-rights safeguards absent from religion-based models. Implementation in Indonesia requires national standardisation of subnational formalisation, operationalisation of limitation clauses, safeguards against discriminatory application, and strengthening constitutional oversight.